2012
DOI: 10.1088/1742-5468/2012/05/p05007
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of circular interface fluctuations in an off-lattice Eden model

Abstract: Scale-invariant fluctuations of growing interfaces are studied for circular clusters of an off-lattice variant of the Eden model, which belongs to the (1 + 1)-dimensional Kardar-Parisi-Zhang (KPZ) universality class. Statistical properties of the height (radius) fluctuations are numerically determined and compared with the recent theoretical developments as well as the author's experimental result on growing interfaces in turbulent liquid crystal [K. A. Takeuchi and M. Sano, arXiv:1203.2530]. We focus in parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 55 publications
10
93
1
Order By: Relevance
“…Similar results were also obtained for the off-lattice Eden model simulations in 2-d [286]. These radial exponents are thus considerably smaller than the corresponding exponents in the (1 + 1) dimensions with a flat substrate [280]: θ + 0 = 1.18 ± 0.08 and θ − 0 = 1.64 ± 0.08.…”
Section: Persistence Properties In Flat Versus Radial Geometrysupporting
confidence: 82%
“…Similar results were also obtained for the off-lattice Eden model simulations in 2-d [286]. These radial exponents are thus considerably smaller than the corresponding exponents in the (1 + 1) dimensions with a flat substrate [280]: θ + 0 = 1.18 ± 0.08 and θ − 0 = 1.64 ± 0.08.…”
Section: Persistence Properties In Flat Versus Radial Geometrysupporting
confidence: 82%
“…In particular, for the BD model in d = 1 + 1, exponents in agreement with the KPZ ones were obtained through appropriated extrapolations of effective exponents [29] and, more recently, from extremely large-scale simulations accessing the regimes where corrections become negligible [30]. Moreover, recent studies of height distributions have given additional proofs of the KPZ universality of Eden and BD models in d = 1 + 1 [16][17][18][19]. For Eden models, scaling exponents and height distributions consistent with KPZ class were also found in d = 2 + 1 [24,31].…”
Section: Introductionmentioning
confidence: 87%
“…(1)], Γ is a nonuniversal constant associated to the amplitude of the interface fluctuations, β is the growth exponent, and χ is a stochastic quantity given by Tracy-Widom [13] distributions. This conjecture was confirmed in distinct KPZ systems [14][15][16][17][18][19] besides exact solutions of KPZ equation [20][21][22][23]. Recent numerical simulations have shown that the KPZ ansatz can be generalized to 2+1 [24][25][26] and higher [27] dimensions, but the exact forms of the asymptotic distributions of χ are yet not known.…”
Section: Introductionmentioning
confidence: 89%
“…We mention that, aside from some early works [101,102,103], and more recently [104], there has been little direct effort on numerical integration of 2d KPZ equation in polar coordinates; see, too [105,106,107]. Indeed, all work on this subclass, aside from radial Eden model simulations [108,109], have resorted to difficult, somewhat frustrating pt-pt simulations of various KPZ/DPRM models [110,65] in what is, effectively, constrained wedge geometries. The frustration arises because, in contrast to simulations for the flat KPZ subclass where all substrate points contribute to the ensemble average, the pt-pt Monte Carlo yields a few datum only per realization.…”
Section: An Homage To Psmentioning
confidence: 99%